Estrogenic activity of ethyl gallate and its potential use in hormone replacement therapy. (15th May 2021) - Lee, Hesol; Lee, Sullim; Baek, Ji Yun; Seo, Chang-Seob; Yun, Hwayoung; Kim, Su-Nam; Kang, Ki Sung; Choi, You-Kyung
Graphical abstract: Abstract: We aimed to compare the estrogenic activities of compounds isolated from Moutan Cortex Radicis (MRC, Paeonia suffruticosa Andrews) and identify their potential use in hormone replacement therapy. We quantified seven marker components (gallic acid, oxypaeoniflorin, paeoniflorin, ethyl gallate, benzoic acid, benzoylpaeoniflorin, and paeonol) in MRC using a high-performance liquid chromatography simultaneous analysis assay. To investigate the estrogenic activity of MRC and the seven marker components, an E-screen assay was conducted using the estrogen receptor (ER)-positive MCF-7 human breast cancer cell line. Among them, ethyl gallate caused cell proliferation in a concentration-dependent manner at concentrations above 25 µM and was clearly suppressed by combination treatment with the ER antagonist ICI 182, 780. Therefore, ethyl gallate may be a compound of MRC that can increase the estrogenic effect in ER-positive MCF-7 cells.